Kajian Teknik Pengurusan Risiko Kelewatan Kerja di Projek Lebuh Raya Pan Borneo dari Padangan Kontraktor - Puddin, Asyraf Naim; Sarpin, Norliana; Mohamed, Sulzakimin; Seow, Ta Wee; Sabtu@Othman, Hilyati; Mohd Sarman, Asmawan (Research in Management of Technology and Business, 2026)
Mega infrastructure projects such as the Pan Borneo Highway serve as a major catalyst for economic growth and regional development in East Malaysia. However, delays in the implementation of this project have frequently become a critical issue that affects time efficiency, cost performance, and construction quality. Therefore, this study was conducted with the objectives of identifying the main factors contributing to work delays in the construction of the Pan Borneo Highway, examining the risk management techniques employed by the project team to address these issues, and proposing improvements to risk management strategies to ensure more efficient implementation of mega projects in the future. The scope of the study focuses on one of work package under the Pan Borneo Highway project in Sabah, namely Package WP04 (Papar–Donggongon). This study adopts a qualitative research approach through semi-structured interviews with three respondents who were directly involved in the implementation of the Pan Borneo Highway project. The qualitative data were analysed using thematic analysis to identify patterns and themes related to risk management and work delays. The study findings show that construction project delays are influenced by several key factors, namely land acquisition and clearance issues, lack of skilled labour, changes in scope of work, adverse weather factors, and delays in the approval and bureaucracy processes. In addition, dynamic rescheduling, the use of real-time site monitoring technology, the formation of a Technical Risk Committee, and training and increasing the capacity of local workforce can have a positive impact on the smoothness, efficiency and effectiveness of construction project management and reduce the risk of repeated delays. Furthermore, the study findings also show that strategies such as emphasising early stages of the project through comprehensive early planning, local workforce capacity development, tighter design change control, the use of weather early warning systems, and flexible work scheduling have been identified as having the potential to reduce project delays. In addition, bureaucratic coordination between relevant agencies is also important to expedite the approval process and improve the efficiency of construction project management. In overall, the findings of this study are expected to provide useful guidance to stakeholders in the construction industry in planning and implementing delay risk management more systematically, thereby supporting the smoother execution of mega infrastructure projects in the future.